PENANAMAN BENIH SORGUM DALAM KEGIATAN PENGABDIAN DESA DI DESA GUNUNGMANIK, KUNINGAN - Haris, M Rahadian Haris; Alfarisi, M Alwi; Raihan, M Zhian; Alfarisi, Alwi; N, Hary Nugraha Azhar; R, M Khaerul; Pahlevi, Rifki Rachman; HF, Attala Dava; Ramadhan, Muhammad Iqbal; Apriyanti, Siti Apriyanti; Djulfiyah, Aldi; S, Subhan; Riyanto, Farhan Dwi; Riyanto, Saniri; Susilo, Ryvaldi Zuwansah Susilo (Unmuh Babel Press, 2025)
Abstract Sorghum (Sorghum bicolor) is a plant native to East Africa in the Abessinia region, Ethiopia, and surrounding areas (Vavilov 1926), which is now a cosmopolitan plant spreading throughout the world. FAO data in 2012 shows that there are 110 countries in the world that grow sorghum. Indonesia, which has been growing sorghum since the early 4th century, is not listed on the FAO list of sorghum producing countries, probably because the harvested area is very small (FAO 2013). In Indonesia, the harvest area of sorghum plants in 1990-2010 was only about 25,000 ha and scattered, so it was not included in the FAO statistical list. Sorghum plants in Indonesia are pushed by commodities with higher economic value, such as sorghum, mung beans, gogo rice, or cassava. Currently, the world is experiencing a food crisis due to soaring prices. The Food and Agriculture Organization (FAO) said that the world food price index was at the level of 159.3 in March 2022. This figure is the highest level since 1990. The food crisis is also exacerbated by Russia's invasion of Ukraine, which has an impact on the global economy, especially disruptions in food and energy supplies. Where 22 countries have stopped exporting food to other countries. Russia, Ukraine and India have also stopped exporting their wheat. As a result, the price of wheat has increased by 3 times. Therefore, to anticipate the need for large wheat, it is necessary to substitute wheat with sorghum. Where sorghum as one of the local food commodities is very strategic and has high economic value, starting from stems, leaves to seeds Keywords: Gunungmanik Village; planting sorghum seedlings; Socialization; Village Service Abstrak Sorgum (Sorghum bicolor) merupakan tanaman asli Afrika Timur di wilayah Abessinia, Ethiopia, dan sekitarnya (Vavilov 1926), yang kini menjadi tanaman kosmopolitan menyebar ke seluruh dunia. Data FAO tahun 2012 menunjukkan terdapat 110 negara di dunia yang menanam sorgum. Indonesia yang sudah menanam sorgum sejak awal abad ke-4 justru tidak tercantum pada daftar negara produsen sorgum FAO, kemungkinan karena luas areal panennya sangat kecil (FAO 2013). Di Indonesia, luas panen tanaman sorgum pada tahun 1990-2010 hanya sekitar 25.000 ha dan tersebar, sehingga tidak masuk dalam daftar statistik FAO. Tanaman sorgum di Indonesia terdesak oleh komoditas yang bernilai ekonomi lebih tinggi, seperti Sorgum, kacang hijau, padi gogo, atau ubi kayu. Saat ini dunia tengah mengalami krisis pangan akibat harga yang melonjak. Food and Agriculture Organization (FAO) menyampaikan data, indeks harga pangan dunia telah berada di level 159,3 pada Maret 2022. Angka tersebut merupakan level tertinggi sejak tahun 1990. Krisis pangan juga diperparah oleh invasi Rusia ke Ukraina, yang berdampak terhadap perekonomian global, terutama gangguan pasokan pangan dan energy. Dimana sudah 22 Negara yang menghentikan ekspor pangan nya ke negara lain. Rusia, Ukraina dan India juga sudah tidak lagi mengekspor gandumnya. Akibatnya harga gandum sampai 3 kali lipat. Oleh karena itu untuk mengantisipasi kebutuhan gandum yang besar perlu mensubstitusi gandum dengan sorgum. Dimana Sorgum sebagai salah satu komoditas pangan lokal yang sangat strategis dan memiliki nilai ekonomis yang tinggi, mulai dari batang, daun hingga biji